2020
DOI: 10.1097/jcma.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-421 predicts poor prognosis and promotes proliferation, migration, and invasion of papillary thyroid cancer cells

Abstract: Background: Papillary thyroid carcinoma (PTC) represents the most frequent subtype of thyroid cancer (TC) with poor prognosis mainly due to the severe invasion and metastasis. As an oncogene, microRNA-421 (miR-421) is involved in the development of various cancers. This study was to investigate the clinical significance of miR-421 in PTC and its effects on the biological function of PTC cells. Methods: The expression level of miR-421 in all tissues and PTC cell lines wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…MYCN also suppresses ATM expression via its upregulation of hsa-miR-421 (Fig. 5), which promotes neuroendocrine prostate cancer cells' invasion and migration potential 30,31 . MYCN was found to stimulate rat fibroblast cells' S phase entry and their transformation into a more proliferative form with rapid cell-cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…MYCN also suppresses ATM expression via its upregulation of hsa-miR-421 (Fig. 5), which promotes neuroendocrine prostate cancer cells' invasion and migration potential 30,31 . MYCN was found to stimulate rat fibroblast cells' S phase entry and their transformation into a more proliferative form with rapid cell-cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study showed that has-mir-421 was highly expressed in lung cancer cells [ 63 ]. Furthermore, it has been demonstrated that the overexpression of has-mir-421 is a prognostic biomarker for non-small cell lung cancer and encourages tumor growth [ 64 ]. Considering these findings from existing studies, the estimation results by Multi-PEN are supported.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, miR-421 was verified as a target miRNA of SNHG1. miR-421 was found to participate in the development of many types of tumors, such as ovarian cancer and papillary thyroid cancer [30, 31]. Moreover, miR-421 has been reported to aggravate inflammatory response in various diseases, such as bronchopulmonary dysplasia [32] and rheumatoid arthritis [33].…”
Section: Discussionmentioning
confidence: 99%